Political Moods Film Melodrama and the Cold War in the Two Koreas - Workman, Travis (University of California Press, 2023)
Melodrama films dominated the North and South Korean industries in the period between liberation from Japanese colonial rule in 1945 and the hardening of dictatorship in the 1970s. The films of each industry are often read as direct reflections of Cold War and Korean War political ideologies and national historical experiences, and therefore as aesthetically and politically opposed. However, Political Moods develops a comparative analysis across the Cold War divide, analyzing how films in both North and South Korea convey political and moral ideas through the sentimentality of the melodramatic mode. Travis Workman reveals that the melancholic moods of film melodrama express the somatic and social conflicts between political ideologies and excesses of affect, meaning, and historical references. These moods dramatize the tension between the language of Cold War politics and the negative affects that connect cinema to what it cannot fully represent. The result is a new way of historicizing the cinema of the two Koreas in relation to colonialism, postcolonialism, war, and nation building. "Deftly employing melodrama not so much as a genre as a domain of affect, Travis Workman provides a pathbreaking new framework for understanding post‑1945 Korean film. An important and highly original work." - MICHAEL K. BOURDAGHS, University of Chicago "In this bracing reading of melodramatic form in Korean films, Workman raises a bold question that haunts Korean studies: how to develop a comparative understanding of the vastly different scenarios in the films of North and South? His answer drives our attention to the subject of mood. A stupendous contribution to the scholarship on Korean cinema, Cold War culture, and melodrama studies." - JINSOO AN, author of Parameters of Disavowal: Colonial Representation in South Korean Cinema